Q: Solve 3x - 5x plus 11x equals -81?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

11x + 8 = 8x + 20 3x + 8 = 20 3x = 12 x = 4

x = -11

(3x-4)(x+5)

3x+5y+8x+2y combine 3x and 8x to get 11x 11x+5y+2y combine 5y and 2y 11x+7y is the answer.

3x + y + 1 = 0y = - 3x - 12x - 3y + 8 = 03y - 2x - 8 = 03y = 2x + 8y = 2x/3 + 8/3-3x - 1 = 2x/3 + 8/3-9x - 3 = 2x + 8-11x = 11x = -1y = -3x - 1 = 3 - 1 = 2The graphs intersect at the point (-1, 2).

Related questions

-3x + 6 + 15x =11x + 8 ie -3x + 15x - 11x = 8 - 6 ie x = 2

11x + 8 = 8x + 20 3x + 8 = 20 3x = 12 x = 4

x=12

11x = 8x-6.............. 11x-8x = -6................... 3x= -6 x = -2

x = -11

8x - 9 = 11x + 12 8x = 11x + 21 -3x = 21 x = -7

(3x-4)(x+5)

8x - 5 + 3x + 17 = 155% 11x + 12 = 1.55 11x = 1.55 - 12 = -10.45 x = - (10.45/11) = - 0.95

6x^2 + 11x + 4 is a Quadratic Statement. It is NOT an equation, because there is no 'equals' (=). It will factor to ( 3x + 4)(2x + 1)

3x+5y+8x+2y combine 3x and 8x to get 11x 11x+5y+2y combine 5y and 2y 11x+7y is the answer.

-11

3x-7 = 14x-29 29-7 = 14x-3x 22 = 11x x = 2 Hope that helps!!;)